Bertrand Russell’s psychology of happiness - García, José E. (2025)
Bertrand Russell (1872-1970), British philosopher, is one of the outstanding intellectual references of the 20th century. Throughout his career, he demonstrated great knowledge in many fields, but his main areas of activity were philosophy, university teaching, and social activism, with a concern for both the complex and abstract issues of philosophy and everyday concerns that plague the modern world. Russell's considerable breadth of interests also brought him closer to various topics of relevance to modern psychology, including the issue of happiness. Russell dealt with the characteristics of the happy person at a time when this problem was still far from being a regular topic in psychology and when its inclusion in the usual reflections of philosophy was still infrequent. This article analyzes Russell's thought in relation to happiness and its relevance as a part of the human experience, as well as his theories regarding its nature and significance. The analysis of this article is theoretical and is based on a discussion of the sources published by Russell on happiness and its meaning for the human experience.